Research on enzootic lymphatic leucosis of cows. - ΠΑΠΑΔΟΠΟΥΛΟΣ, E.; ΣΕΪΤΑΡΙΔΗΣ, K. (Journal of the Hellenic Veterinary Medical Society, 2019)
An hematological study has been carried out on 372 cows, 2 or more years old, of the friesian race belonging to 40 breedings in the Attica region. Only one cow (0,27%), 6 years old, was positive for enzootic lymphatic leucosis with the hematological method (9.500 lympocytes /μΙ of blood).